Securitization in Chinese climate and energy politics. (24th January 2016) - Nyman, Jonna; Zeng, Jinghan
Abstract : This article provides an overview of securitization in Chinese climate and energy debates. Scholars have debated the merits as well as the potentially problematic implications of securitization, or framing issues as 'security, ' since the early 1990s. Early concern focused on the potential problems with linking environmental issues with 'security, ' and the debate has since also turned specifically to the climate and energy. However, it is only recently that this debate has begun to pay attention to China. Energy and climate concerns are of increasing importance to China: the sheer scale of its energy consumption and air pollution struggles dwarf the challenges seen by other states, and its policy choices play a key role in shaping global climate and energy dynamics. Thus, while securitization in the Chinese context is rarely studied, how China frames its energy and climate policy matters. Both energy and climate are taken increasingly seriously, and security plays an increasing role in debates. This review surveys the increasing popularity of linking security with climate and energy issues both in the academic debate on China and in official discourse, and some of the potential implications. WIREs Clim Change 2016, 7:301–313. doi: 10.1002/wcc.387 This article is categorized under: Policy and Governance > National Climate Change Policy